Outpatient Parotidectomy, a Safety and Financial Review. (February 2022) - Scher, Maxwell; Cabrera, Claudia I.; Cai, Yida; Tamaki, Akina; Li, Shawn; Fowler, Nicole; Rezaee, Rod; Lavertu, Pierre; Teknos, Theodoros; Thuener, Jason
Objective: The objective of this study is to investigate the safety, efficacy, and potential cost-savings of the outpatient parotidectomy procedure. Methods: This is a retrospective chart review of all patients who underwent a parotidectomy at a large academic center from 2015 through 2019 including demographic data, postoperative complications, drain placement, readmission, and financial cost. A comparison was performed between patients who underwent an outpatient vs inpatient parotidectomy. Results: A total of 335 patients underwent parotidectomy (136 outpatient; 199 inpatient). Comparison of patient demographics, common comorbidities, tumor size, tumor type, postoperative complications, and readmission rate was similar between the inpatient and outpatient cohorts. The overall mean cost difference between inpatient parotidectomy and outpatient parotidectomy for all years was $1528.58 (95%CI: $1139-$1916). Conclusion: The outpatient parotidectomy procedure has a comparable safety profile to the inpatient procedure while providing a significant cost-savings benefit.